Transformation of physical characteristics in fired clay bricks by adopting waste-based fluxing agent / Mazlini Mazlan... [et al.] - Mazlan, Mazlini; Abdul Wahab, Rabiatul Adawiyah; Sanusi, Nur Syafiqa Hamiza; Mohd Nasli, Nur Hanis Syazwani; Junaizi, Nurul Athirah Balqis (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
The current practices in the recent development of fired clay brick (FCB) by adopting waste materials have tremendously reduced the usage of the primary source of FCB, which is clay soil (CS). In this study, the main objective is to reduce the utilisation of CS as the main component in the FCB-making process. Other waste materials such as soda lime silica (SLS) glass bottles, and sea shells (SS) were also added into the precursor admixtures. The admixtures containing CS, SLS and SS were mixed according to the empirical formula of (1-x)[40SLS - 60CS]: x[SS] = 0, 10, 20, 30, 40 wt.%. A batch of 40 g mixture was prepared, and 21% water was added. The admixtures were mixed, moulded into a rectangular brick shape, and dried before the sintering process at 850 °C. The physical properties of the FCB were investigated as a function of the SS content in the form of apparent density, linear shrinkage, loss of ignition and plasticity. As a result, the apparent density and loss of ignition of the FCB increased from 1.91 gcm-3 to 2.31 gcm-3 and 10.60 % to 20.81%, respectively. The linear shrinkage and plasticity percentage decreased from 2.50% to 2.27% and 11.01% to 8.70% with an increase of SS content. This study has uncovered the above findings, and has demonstrated a promising discovery of the SS as a possible substitute in FCB.